2017
DOI: 10.1073/pnas.1712511114
|View full text |Cite
|
Sign up to set email alerts
|

Control of growth and gut maturation by HoxD genes and the associated lncRNA Haglr

Abstract: SignificanceDuring development, transcription factors are necessary not only to pattern the body plan but also to control growth. However, the link between these two developmental components has been difficult to establish. Hox genes are involved in the emergence of a functional digestive system in metazoans, thus providing a potential impact on growth through nutrition. Also, genetic conditions involving these genes lead to important growth retardation. We analyzed several targeted mutant lines at the HoxD lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Read-through transcription of the lncRNA SVALKA may provide a mechanism to invade and break positive feedback mechanisms reinforcing CBF1 transcription. As lncRNA transcription in yeast and mammalian cells correlate with the boundaries of chromatin domains, roles of lncRNA in communicating regulation across domain boundaries may be common despite differences in genomic topologies 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Read-through transcription of the lncRNA SVALKA may provide a mechanism to invade and break positive feedback mechanisms reinforcing CBF1 transcription. As lncRNA transcription in yeast and mammalian cells correlate with the boundaries of chromatin domains, roles of lncRNA in communicating regulation across domain boundaries may be common despite differences in genomic topologies 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Read-through transcription of the lncRNA SVALKA may provide a mechanism to invade and break positive feedback mechanisms reinforcing CBF1 transcription. As lncRNA transcription in yeast and mammalian cells correlate with the boundaries of chromatin domains, roles of lncRNA in communicating regulation across domain boundaries may be common despite differences in genomic topologies 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be verified if this Foxp1/lncRNA axis is also functionally important in a spinal cord context. An array of studies in various cell models has demonstrated regulation of Hox genes by lncRNAs such as Hotair, Hottip and Haglr [118,149,160]. However, to date, only one study has established a link between the roles of lncRNAs in MN development and Hox regulation.…”
Section: Lncrnas In the Regulation Of Postmitotic Neuronsmentioning
confidence: 99%